PENERAPAN CHALLENGE-BASED LEARNING DALAM UPAYA MENINGKATKANKEMAMPUAN PEMAHAMAN KONSEPMATEMATIKA SISWA SMA - Arif Abdul Haqq (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2016)
This Research examined students's understanding of mathematical concepts ability. Samples are tenth grade students in one of state high school in Cirebon City. Experiment class received Challenge-based Learning (CbL) approach while control class received Conventional Approach.The instrument used was understanding of mathematical concepts ability test. The data earned were analyzed statistically. The results showed that students's understanding of mathematical concepts ability who receivedÂ CbL approach is better than students who received conventioanl approach (1/2 sig = 0.0005<0.05). In term indicators of understanding of mathematical concepts,highest enhancement that achieved by students was indicator of classify objects based on fulfilled or not requirements that form that concept, while the lowest enhanchment that achieved by students was indicator of make example or counter example from the concept learned.